2003
DOI: 10.1364/oe.11.000824
|View full text |Cite
|
Sign up to set email alerts
|

Localized pulsed laser interaction with submicronic gold particles embedded in silica: a method for investigating laser damage initiation

Abstract: Laser damage phenomena in fused silica are currently under study because of numerous related high power laser applications. Nanosized defects are believed to be responsible for some laser damage initiation. In order to predict and to quantify this initiation process, engineered submicronic gold defects were embedded in silica. The study of these samples by localized pulsed irradiation of isolated gold particles coupled with Nomarski, atomic force and photothermal microscope observations permits us to discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Many experiments have shown that the damage morphologies initiating from real and artificial nanoabsorbing defects are very similar. Thus, an alternative approach to study laser interaction with nano-absorbing defects is to introduce artificial nano-absorbing defects inside the coatings [73][74][75]. Gold nanoparticles are the preferred choice for artificial absorbing defects because of their well-known optical and thermal characteristics, chemical stability, and availability in the form of gold colloids or powders.…”
Section: Interpretation Of Crater Formationmentioning
confidence: 99%
“…Many experiments have shown that the damage morphologies initiating from real and artificial nanoabsorbing defects are very similar. Thus, an alternative approach to study laser interaction with nano-absorbing defects is to introduce artificial nano-absorbing defects inside the coatings [73][74][75]. Gold nanoparticles are the preferred choice for artificial absorbing defects because of their well-known optical and thermal characteristics, chemical stability, and availability in the form of gold colloids or powders.…”
Section: Interpretation Of Crater Formationmentioning
confidence: 99%
“…One possibility is electric field enhancement on inclusion, scratches 2 or self focusing induced by thermal effect or non linearity. Another possibility mainly reported 3,4,5 is the laser damage initiation through local absorption. In this case the local heating can be extended to the surrounding material and reach a critical temperature then lead to a plasma formation and subsequent shockwave.…”
Section: Introductionmentioning
confidence: 99%
“…Different theoretical and experimental studies have shown in nanosecond regime that absorbing nanometer-sized particles are responsible for the initiation of the damage process. [1][2][3][4] In most cases these defects are not identified since they may have nanoscale size and be distributed at low concentration. In the case of surface damage, the precursors could be contaminants coming from the steps of polishing, [5][6][7][8] cleaning, and also from the deposition techniques and materials involved in the coatings.…”
Section: Introductionmentioning
confidence: 99%